Vertragsnetze und Netzzweck - Güttler, Nina Marie (Studien zum Handels-, Arbeits- und Wirtschaftsrecht, 2022)
Highly relevant in practice and challenging in terms of legal theory: contractual networks of independent businesses are widespread and diverse in modern business life. But what does "contractual business network" actually mean? How does it differ from other forms of cooperation, especially those under corporate law? Who is liable and how? Nina Marie Güttler succeeds in making contractual networks distinguishable on the basis of their legal, economic and sociological foundations and in classifying them dogmatically in German law. For franchise practice, she translates the insights gained into specific rights and obligations of franchisees. A work that is equally interesting for academia, the judiciary and the advocacy.